DOPPLER DATA IN PREGNANT WOMEN WHO HAVE COVID-19 (World Bulletin of Public Health, 2023)
Of the obstetric outcomes in pregnant women with a history of COVID19, the most common were premature birth, which amounted to 13.7%, and a high incidence of severe preeclampsia, which amounted to 18.3%. The incidence of premature birth in pregnant women with severe COVID-19 at 22- 28 weeks was significantly more than 8 times higher than in pregnant women with mild COVID-19
Keywords: cytokines; fetus; obesity